Mitigasi Risiko Limbah Plastik pada Reverse Logistik Network - Agnestia, Treza; Evi Yuliawati (2477 - 6165, 2021)
Plastic waste actually will still have a high sale value if it is utilized well or recycled to be products with better values. Unfortunately, the recycle process of plastic waste has some obstacles such as the lack of people’s understanding on the waste. Therefore, identification is indispensable to conduct on the risk that potentially disrupt the Reverse Logistic Network (RLN). This research was carried out through House of Risk (HOR) method consisting of 2 phases. HOR phases 1 was the phase for identifying the risks and their agents. Next, the researcher measured the levels of severity and occurrence as well as calculated the value of Aggregate Risk Priority (ARP). All of those stages ware used to investigate the selected risk agents and design mitigation action on HOR phase 2. The results of research and calculation obtained 29 risk event, 52 risk agent, and 3 selected risk agents for mitigation action.